Dynamic characteristics analysis and experimental of differential dual drive servo feed system. (December 2021) - Yu, Hanwen; Zhang, Laigang; Wang, Chong; Feng, Xianying
This paper presents the design for a new differential-dual-drive low-speed micro-feed mechanism. The 'nut rotary ball screw pair' is the main driving component of the mechanism. The screw and nut are each driven by a servo motor and these motors rotate in the same direction at a similar speed. The nonlinear factors such as friction and backlash can lead to unstable behaviours such as stick-slip and oscillation of the feed system. We use the Euler–Bernoulli beam elements, which have axial and torsional degrees of freedom, to describe the axial and torsional vibration of the ball screw, and use the spring-lumped parameter method to analyse other components of the feed system. An electromechanical coupling dynamic model with nonlinear factors of friction and clearance is established. Through simulation analysis and experiment, the difference in response of single-drive and differential-dual-drive systems under the influence of friction and clearance is studied. The results show that the nonlinear factors of friction and clearance have an influence on the feed speed of single-drive and differential-dual-drive system, but the low-speed micro-feed performance of the differential-dual-drive system is evidently better than that of the single-drive system. In the experiment, under the condition of screw single drive and differential dual drive, the critical crawling velocities of the table are measured. The experimental results are consistent with the simulation results, which verifies that the established models are reasonable. This lays a foundation for the design and research of the controller.